Pengaruh Terapi Bermain Plastisin Terhadap Penurunan Kecemasan Akibat Hospitalisasi Pada Anak Usia Prasekolah (3-6 Tahun) Di Rumah Sakit Bhayangkara - Dismawati, Yeni; Ramlis, Ravika; Aprianti, Delta (Utami Publisher, 2025)
Hospitalization in preschool children (3–6 years) can cause anxiety due to environmental changes, medical procedures, and limited social interaction. One effort that can be done to reduce this anxiety is with play therapy. This study aims to determine the effect of play therapy with plasticine on reducing anxiety levels in preschool children undergoing treatment at Bhayangkara Hospital. This study design uses a quantitative method with a quasi-experimental approach, pre-test and post-test with an intervention group. The sample consisted of 41 children aged 3–6 years who were divided, selected by total sampling technique. Measurement of anxiety levels was carried out using an observation sheet based on children's anxiety indicators. The results of data analysis showed that the level of anxiety in children due to hospitalization before being given therapy was 100% of all respondents experienced moderate anxiety. After being given therapy, the majority of respondents, 87.8%, experienced mild anxiety. The p value is 0.001 because p <0.05. This means that the effect of play therapy with plasticine on reducing anxiety due to hospitalization in preschool children (3–6 years) at Bhayangkara Hospital Bengkulu. Plasticine play therapy has been shown to be effective as a non-pharmacological intervention to reduce anxiety caused by hospitalization in preschool-aged children. It is hoped that this therapy can be implemented as part of pediatric nursing care in hospitals.